Analyzing Factors Influencing the Success of Currency Redenomination in Indonesia: A Literature Review - Intan Anindya Pramytha; Ula Restu Rafifah; Atika Jauharia Hatta; Alfredo Dos Santos; Frasto Biyanto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study aims to analyze the factors that affect the success of currency redenomination, focusing on the Indonesian context. The method used was a literature study in which 30 articles related to redenomination were reviewed to understand this topic comprehensively. The study results showed that factors such as inflation rate, risk of redenomination, public understanding, currency changes, and psychographic aspects significantly affected the success of redenomination. The contribution of this research lies in providing an in-depth analysis of the implementation of redenomination in Indonesia and policy recommendations that can aid in successful implementation, as well as providing a broader perspective on the practice of redenomination in various economic contexts.